2022
DOI: 10.1515/tnsci-2022-0226
|View full text |Cite
|
Sign up to set email alerts
|

Psychobiotics improve propionic acid-induced neuroinflammation in juvenile rats, rodent model of autism

Abstract: This study aimed to evaluate the protective and therapeutic potency of bee pollen and probiotic mixture on brain intoxication caused by propionic acid (PPA) in juvenile rats. Five groups of six animals each, were used: the control group only receiving phosphate-buffered saline; the bee pollen and probiotic-treated group receiving a combination of an equal quantity of bee pollen and probiotic (0.2 kg/kg body weight); the PPA group being treated for 3 days with an oral neurotoxic dose of PPA (0.25 kg/kg body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Notably, when compared to control mice, PS128 treatment markedly raised dopamine and serotonin levels in the striatum and prefrontal cortex (Liu et al, 2015(Liu et al, , 2016. A different study discovered a novel method for the advantageous application of probiotics and bee pollen in the context of neuroinflammation caused by cytokine alterations and the potential involvement of glial cells in the gut-brain axis (Alonazi et al, 2022). In 1954, Brock Chisholm made the foresighted statement that "No physical health without mental health" (Kolappa et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, when compared to control mice, PS128 treatment markedly raised dopamine and serotonin levels in the striatum and prefrontal cortex (Liu et al, 2015(Liu et al, , 2016. A different study discovered a novel method for the advantageous application of probiotics and bee pollen in the context of neuroinflammation caused by cytokine alterations and the potential involvement of glial cells in the gut-brain axis (Alonazi et al, 2022). In 1954, Brock Chisholm made the foresighted statement that "No physical health without mental health" (Kolappa et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Another HDAC inhibitor, vorinostat, ameliorated impairments in sociability and cognitive memory in an Ash1L-deletion-induced ASD/ID mouse model [197]. In addition to butyrate and/other HDAC inhibitors, studies are increasingly pointing to the potential utility of probiotics or, in some instances, psychobiotics, a combination of bee pollen and probiotics in ASD [198]. Moreover, dietary therapies composed of prebiotics (artichoke and Luteolin) and probiotics (yogurt and Lacticaseibacillus rhamnosus GG) led to improvements in oxidative stress and neuroinflammation, biochemical characteristics of ASD, in a rat model of ASD [199].…”
Section: Implications For Novel Interventions In Asdmentioning
confidence: 99%
“…In particular, this study also showed that psychobiotic treatment decreased serum pro-inflammatory cytokine, IL-6 levels, and increased anti-inflammatory cytokine, IL-10 levels, with the improved status of diverse behavior tests including social interaction, anxiety, and repetitive behaviors ( Adıgüzel et al., 2022 ). Alonazi also demonstrated that dietary psychobiotic supplementation could reduce levels of various serum inflammatory cytokines, such as IL-1β, IL-8, IL-10, and IFN-γ, in an ASD rat model induced by a neurotoxic dose of propionic acid ( Alonazi et al., 2022 ).…”
Section: Psychobiotics: Potential Roles On Mgb Axis As Treatment Targetmentioning
confidence: 99%